2016
DOI: 10.1371/journal.pone.0167253
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Costs of Reappraisal Depend on Both Emotional Stimulus Intensity and Individual Differences in Habitual Reappraisal

Abstract: Recent models of emotion regulation suggest that the cognitive costs of reappraisal depend on stimulus intensity and habitual reappraisal. In the current experiment, we tested these hypotheses by manipulating the intensity of unpleasant and pleasant images, which participants reappraised, viewed, or suppressed their emotions to. To assess cognitive costs, we measured participants’ performance on a concurrent simple reaction time task. Participants also reported on their everyday use of reappraisal and suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 39 publications
4
48
0
Order By: Relevance
“…Many have argued that the successful use of reappraisal requires several potentially taxing cognitive processes, including working memory, task switching, and the ability to override a prepotent response (Gan, Yang, Chen, Zhang, & Yang, 2017; Hofmann, Schmeichel, & Baddeley, 2012; Ortner, Ste Marie, & Corno, 2016). For example, Ortner and colleagues (2016) suggested that reappraisal in emotionally intense situations may be particularly difficult because the individual will experience a conflict between the initial (often negative) appraisal and the new, less emotionally evocative reappraisal. As the emotional intensity of a situation increases, it may become increasingly difficult to override the original appraisal of the situation.…”
Section: Cognitive Reappraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Many have argued that the successful use of reappraisal requires several potentially taxing cognitive processes, including working memory, task switching, and the ability to override a prepotent response (Gan, Yang, Chen, Zhang, & Yang, 2017; Hofmann, Schmeichel, & Baddeley, 2012; Ortner, Ste Marie, & Corno, 2016). For example, Ortner and colleagues (2016) suggested that reappraisal in emotionally intense situations may be particularly difficult because the individual will experience a conflict between the initial (often negative) appraisal and the new, less emotionally evocative reappraisal. As the emotional intensity of a situation increases, it may become increasingly difficult to override the original appraisal of the situation.…”
Section: Cognitive Reappraisalmentioning
confidence: 99%
“…Sheppes and Meiran (2007) found that reappraisal is less effective at changing the experience of negative emotions in intense emotional situations. In addition, people are less likely to choose to use reappraisal in emotionally intense situations (Sheppes et al, 2014), and the use of reappraisal is associated with decreased self-control resources and decreased performance on reaction time tasks when used in high-intensity situations (Ortner et al, 2016; Sheppes & Meiran, 2008). Studies that investigate the spontaneous use of emotion regulation strategies also suggest that people do not choose to use reappraisal very frequently to regulate their emotions relative to the use of suppression and distraction (Brans, Koval, Verduyn, Lim, & Kuppens, 2013; Suri, Whittaker, & Gross, 2015).…”
Section: Cognitive Reappraisalmentioning
confidence: 99%
“…Just as this is a learned habit ("gut feeling") that is difficult to change instantly, so are emotions. The increased cognitive cost of reappraisal in habitual responses is recognized in modern research but unfortunately does not address cognitive-emotive dissonance (Ortner et al 2016).…”
Section: Psychosomatic Learning Theory and Why What Feels Wrong May Bmentioning
confidence: 99%
“…We expect this effect to be especially strong for those higher (vs. lower) in social anxiety severity, given socially anxious individuals are typically less tolerant of negative affect (Herbert & Cardaciotto, 2005) and may therefore value initial affective relief more. Further, socially anxious individuals' less frequent use of engagement-oriented strategies (Werner et al, 2011) may make engagement-oriented strategies more cognitively taxing when used (Ortner et al, 2016).…”
Section: Study Overview and Hypothesesmentioning
confidence: 99%
“…Importantly, the tendency to rely more heavily on avoidance‐ relative to engagement‐oriented strategies may have implications for short‐term changes in affect (irrespective of perceived effectiveness). For example, Ortner, Marie, and Corno () showed that cognitive reappraisal was associated with greater cognitive costs for those who reported less habitual use of the strategy, suggesting that cognitive reappraisal may be associated with greater depletion for socially anxious (vs. nonanxious) individuals. Thus, the short‐term cognitive “costs” of using engagement‐oriented strategies may be greater for individuals experiencing higher levels of social anxiety, even if avoidance‐oriented ER contributes to increased social isolation or heightened levels of trait social anxiety long‐term.…”
Section: Introductionmentioning
confidence: 99%